Leisure Activities and Their Relationship With MRI Measures of Brain Structure, Functional Connectivity, and Cognition in the UK Biobank Cohort - Anatürk, Melis; Suri, Sana; Smith, Stephen M.; Ebmeier, Klaus P.; Sexton, Claire E. (Frontiers in Aging Neuroscience, 2021)
INTRODUCTION: This study aimed to evaluate whether mid-life and late life participation in leisure activities is linked to measures of brain structure, functional connectivity and cognition in early old age. METHODS: We examined data collected from 7,152 participants of the UK Biobank study. Weekly participation in six leisure activities was assessed twice. Based on responses collected at these two time points, individuals were split into one of four groups: (1) stable and low engagement, (2) stable and weekly engagement, (3) low to weekly engagement and (4) weekly to low engagement. A cognitive battery and 3T MRI brain scan were administered at the second visit. RESULTS: Consistent weekly attendance at a sports club or gym was associated with stronger connectivity between the sensorimotor network, lateral visual and cerebellar networks. Visiting friends and family across the two timepoints was also associated with larger volumes of the occipital lobe. Additionally, stable and weekly computer use was associated with global cognition. No other associations were significant. DISCUSSION: This study demonstrates that not all leisure activities contribute to cognitive health equally, nor is there one unifying neural signature across leisure activities.